The Metaparadigm of Scientific Knowledge and Interdisciplinary Perspectives on Legal Culture - Maksim V. Zaloilo (RUDN Journal of Law)
The purpose of the research is to assess the prospects for applying methods and approaches from the humanities and exact sciences to understand the genesis, prerequisites, patterns, features, trends, and vectors of the evolution of legal culture as a distinct cognitive challenge and a multifaceted phenomenon within state-legal reality. The study employs general scientific (dialectical) and system-structural methods, as well as functional comparison and legal forecasting techniques. It analyzes approaches to understanding interdisciplinarity in scientific research, which is presented as a natural outcome of the gradual development of science and the emergence of a symbiotically interconnected and interdependent metascience in both the modern era and the long term. It identifies the key features of interdisciplinary research planning are substantiates the mobility of disciplinary and cognitive boundaries. The challenges of polysemy in scientific work and the evaluation of research outcomes are highlighted, with a proposed solution involving the expansion of interdisciplinary dialogue. Amid the ongoing disciplinary isolation of individual sciences, the article identifies major research shifts in the field of law, reflecting an increase in the metaparadigmality of scientific knowledge, as evidenced by anthropological, comparative, linguistic, and digital turns. It also highlights varieties of theoretical and practical approaches to applying interdisciplinarity in the idealized theoretical framework of scientific inquiry into legal culture. The relevance of memetics in understanding the evolution of legal culture is emphasized, particularly in relation to the processes of translation, copying, variation, and reproduction of memes in law. The article concludes by outlining the cultural potential of an interdisciplinary approach to studying the phenomenon of legal culture.